Experimental and numerical analysis of the cooling performance of water spraying systems during a fire. - YaoHan Chen; ChungHwei Su; JoMing Tseng; WunJie Li (PLoS ONE)
The water spray systems are effective protection systems in the confined or unconfined spaces to avoid the damage to building structures since the high temperature when fires occur. NFPA 15 and 502 have suggested respectively that the factories or vehicle tunnels install water spray systems to protect the machinery and structures. This study discussed the cooling effect of water spray systems in experimental and numerical analyses. The actual combustion of woods were compared with the numerical simulations. The results showed that although the flame continued, the cooling effects by water spraying process within 120 seconds were obvious. The results also indicated that the simulation results of the fifth version Fire Dynamics Simulator (FDS) overestimated the space temperature before water spraying in the case of the same water spray system.